What a day it was at school! : poems - Prelutsky, Jack (Greenwillow Books, 2006)
Homework (oh, dear!), music, a field trip (hooray!), science, spelling (gasp!), gym, a noisy mistake (oops!). And friends, books, recess, a food fight, math, the infirmary, a visit, history, art, show-and-tell . . . What a funny, outrageous, exciting, incredible, silly, extraordinary day it was at school! Are you ready to read all about it?